‘Zodra wij er zijn, komen de roddels op gang.’ Britse krakers en de strijd om beeldvorming in Leiden tijdens de jaren negentig - Hendriks, Elisa; Nimanaj, Blerina; van der Steen, Bart (TSEG - The Low Countries Journal of Social and Economic History, 2020)
In the early 1990s, several hundreds of predominantly working-class British and Irish youths moved to Leiden to work as seasonal laborers in the region’s floral industry. Because it was difficult to gain access to regular housing, a large number of them squatted houses in and around the city. Local newspapers paid much attention to the British squatters, who were often described as organizers of rave parties, consumers of illicit drugs and causers of noise complaints. The squatters tried to counter this image, but had only limited access to the media. Based on a systematic analysis of 588 Leidsch Dagblad news reports, debates in the local squatter magazine De Peueraar and six semi-structured interviews with British and Leiden squatter veterans, this paper reconstructs the struggle over the image of ‘the’ British squatter in Leiden during the 1990s. It argues that squatters were only moderately successful in countering the image of noisy ‘party squatters’ and presenting themselves as constructive neighborhood activists, in part because the squatter scene moved between social movement and subculture.